A method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology

CN122959677APending Publication Date: 2026-10-23LIAONING UNIVERSITY OF TECHNOLOGY +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610889600.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

一是电解Cu箔密度比较高,增加了电池的整体重量,不利于电池能量密度的提升

Benefits of technology

1、本方案,通过引入锌元素形成 Cu-Zn 合金镀层以代替纯铜使用,降低了集流体的制造成本,同时提高了镀层的柔韧性和延展性,此外锌元素的加入可有效调控锂金属的沉积行为,通过形成均匀的合金化界面抑制锂枝晶的生长,从而提升电池的循环寿命和安全性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959677A_ABST
    Figure CN122959677A_ABST
Patent Text Reader

Abstract

The application relates to the field of corrosion-resistant protective coatings of lithium ion battery negative electrode current collectors, in particular to a preparation method of Cu-Zn@C polymer composite copper foil based on a magnetron sputtering technology, the Cu-Zn@C polymer composite copper foil comprising a polyimide polymer matrix and a Cu-Zn alloy and carbon composite coating layer deposited on the surface of the matrix through the magnetron sputtering technology. The composite coating layer effectively reduces the weight and manufacturing cost of the current collector, improves the anti-spontaneous combustion safety of the lithium battery, and simultaneously endows the composite copper foil with excellent corrosion resistance, flexibility and mechanical strength, so as to meet the performance requirements of high-energy-density lithium batteries on negative electrode current collectors. In addition, the preparation process of the application is simple and convenient to operate, and the prepared composite film has ideal film-substrate adhesion and surface flatness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of corrosion-resistant protective coatings for negative electrode current collectors in lithium-ion batteries, and specifically to a method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology. Background Technology

[0002] With the development of modern society, lithium batteries, due to their high energy density, long cycle life, and environmentally friendly characteristics, have been widely used in various fields such as consumer electronics, electric vehicles, and renewable energy storage, becoming a key driving force for social progress and technological development. However, as the application demands for lithium batteries continue to increase, optimizing lithium battery performance and controlling their production costs have become crucial for technological development. Among these, the selection of negative electrode current collector materials and structural design have a significant impact on lithium battery performance.

[0003] Currently, pure electrolytic Cu foil is mainly used as the negative electrode current collector for lithium batteries. Although it has good conductivity and mechanical strength, it has some drawbacks in practical applications. First, the high density of electrolytic Cu foil increases the overall weight of the battery, hindering the improvement of energy density. Second, the limited flexibility of electrolytic Cu foil makes it prone to stress concentration and cracking during charging and discharging, thus affecting battery cycle life. Third, Cu foil has poor corrosion resistance, high manufacturing costs, high energy consumption during production, and low safety performance. When the battery is punctured, the Cu foil can develop large burrs that puncture the battery separator, causing a direct short circuit between the positive and negative electrodes. Because Cu foil itself has good conductivity and is not easily melted, the current will continue to increase during the short circuit, generating a large amount of heat and further exacerbating the battery temperature rise, thus triggering thermal runaway in lithium batteries. Furthermore, during battery operation, the Cu foil current collector is susceptible to electrolyte corrosion, which can lead to structural damage and functional failure. Therefore, developing a lightweight, flexible, corrosion-resistant, and highly safe negative electrode current collector is of great significance.

[0004] Therefore, a high-adhesion composite copper foil current collector and its preparation method are disclosed in the prior art (CN118553919A), relating to the field of lithium-ion battery technology. This invention uses a polypropylene film as a substrate, enhances the surface polarity of the film through plasma treatment, then sequentially deposits a titanium adhesion layer and a seed copper layer using magnetron sputtering, and finally thickens the foil through electroplating. The resulting composite copper foil effectively reduces the weight of the current collector and increases the energy density of the battery. Furthermore, the introduction of the titanium layer enhances the adhesion between the plating layer and the base film. While this invention improves the film-substrate bonding, the pure copper plating layer has poor corrosion resistance in the electrolyte and is prone to electrochemical corrosion during long-term service, affecting the structural stability and cycle life of the current collector. In addition, this technology does not provide an additional protective layer on the copper surface, and the interfacial chemical stability of the plating layer needs further improvement.

[0005] A prior art method (CN117845285A) discloses a method for preparing a composite copper foil without light-transmitting points, relating to the field of metal materials technology. This invention metallizes a polymer film by double-sided magnetron sputtering to form a dense copper layer, followed by copper electroplating in an acidic electrolyte. The resulting composite copper foil has a dense, light-transmitting copper layer, meeting the performance requirements of downstream applications. Furthermore, the preparation process is more refined and reliable, possessing significant commercial and industrial value, and can further accelerate cost reduction in the lithium-ion battery copper foil industry and improve the safety of power batteries. While this technology improves the density of the copper layer through optimized magnetron sputtering, it still does not consider the corrosion resistance of the pure copper plating in the electrolyte, making it susceptible to electrolyte erosion and structural degradation during long-term use. In addition, this composite copper foil cannot achieve rapid melting during battery short circuits, lacking an effective thermal runaway safety protection mechanism, and its interfacial chemical stability needs further improvement.

[0006] In summary, this invention uses a Cu-Zn alloy coating to replace pure copper for protection, which reduces the manufacturing cost of the current collector, improves the flexibility and ductility of the coating, and utilizes the low melting point of zinc to form a local melting when the battery is damaged by external force or a short circuit occurs, quickly cutting off the current transmission, thereby improving the cycle life and safety performance of the battery. Summary of the Invention

[0007] To address the aforementioned issues, this invention provides a method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology. This method uses a Cu-Zn alloy coating instead of pure copper for protection, reducing the manufacturing cost of the current collector while improving the flexibility and ductility of the coating. Furthermore, it enables localized melting and rapid interruption of current transmission when the battery is damaged by external forces or experiences a short circuit, thereby enhancing the battery's cycle life and safety performance.

[0008] To achieve the above objectives, the technical solution of the present invention is as follows: A method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology, comprising the following steps: S1: The flexible polymer matrix is ​​ultrasonically cleaned; then the ultrasonically cleaned flexible polymer matrix is ​​dried for 0.1-0.2 hours to obtain the dried polymer matrix. S2: The dried polymer matrix is ​​placed in the magnetron sputtering equipment chamber for plasma cleaning. A Cu-Zn alloy is used as the target material, and polymer matrix deposition is performed by vacuum magnetron sputtering coating technology. S3: Using graphite as the target material, a carbon layer is deposited on the surface of the polymer matrix after deposition in S2 to obtain Cu-Zn@C polymer composite copper foil.

[0009] Furthermore, the flexible polymer substrate is a PI film with a thickness of 20-26 µm. During the ultrasonic cleaning process, the flexible polymer substrate is ultrasonically cleaned in anhydrous ethanol and deionized water for 0-0.5 hours respectively.

[0010] Furthermore, in S2, the polymer matrix is ​​subjected to plasma treatment on its surface using a -300V self-biased voltage.

[0011] Furthermore, in S2, the target material is a composite target material with a stepped boss structure.

[0012] Furthermore, the upper substrate of the composite target material with a stepped boss structure is made of Cu-Zn alloy, and the lower substrate is a Cu substrate.

[0013] Furthermore, the dried polymer matrix is ​​suspended by tape in the working chamber of the magnetron sputtering equipment for double-sided deposition.

[0014] Furthermore, in S2, the magnetron sputtering operating parameters are as follows: the distance between the target and the polymer substrate is 100-150 mm, and the vacuum level of the magnetron sputtering equipment chamber is 1.5-3.0 × 10⁻⁶ mm. -3 The sputtering power of the Pa, Cu-Zn alloy target is 100-200W, the coating temperature of the polymer substrate is 26-28℃, the gas flow rate is 30-55 sccm, the coating thickness of the polymer substrate is 700-1000 nm, and the sputtering time is 0.5-1 hour.

[0015] Furthermore, in S3, the magnetron sputtering operating parameters are as follows: sputtering power of graphite target is 100-200 W, sputtering time is 1-3 hours, coating temperature of polymer substrate is 26-28 ℃, gas flow rate is 30-55 sccm, and coating thickness of polymer substrate is 60-200 nm.

[0016] Furthermore, the Cu-Zn alloy is a Cu-Zn 9:1 (wt%) alloy.

[0017] Furthermore, in S3, the overall thickness of the Cu-Zn@C polymer composite copper foil is 26-27 µm.

[0018] The above approach has the following beneficial effects: 1. This solution introduces zinc to form a Cu-Zn alloy coating to replace pure copper, which reduces the manufacturing cost of the current collector and improves the flexibility and ductility of the coating. In addition, the addition of zinc can effectively regulate the deposition behavior of lithium metal and inhibit the growth of lithium dendrites by forming a uniform alloying interface, thereby improving the cycle life and safety performance of the battery.

[0019] 2. In this invention, PI (polyimide) is used as the substrate material, which significantly reduces the cost of Cu raw materials compared to traditional Cu foil applications. Then, magnetron sputtering technology is used to deposit and thicken the substrate, resulting in a dense and uniform Cu-Zn composite film. The prepared Cu-Zn composite film possesses high strength, high flexibility, and ultra-thin properties, while also exhibiting a highly stable composite structure. Furthermore, it reduces the amount of Cu used compared to traditional Cu foil, thus lowering costs.

[0020] 3. This solution refers to the Cu-Zn@C polymer composite copper foil (hereinafter referred to as composite copper foil) of the present invention. Due to the low melting point and flame retardancy of the polymer substrate, when a battery made of composite copper foil is punctured, the composite film is less likely to form burrs or the burrs formed are small. In the event of a short circuit, the thinner metal conductive layer will accelerate local melting like a fuse, thereby playing a role in preventing spontaneous combustion of the battery and improving the safety of use. Attached Figure Description

[0021] Figure 1 This is a process flow diagram of an embodiment of the preparation method of Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology of the present invention; Figure 2 The images show the SEM surface morphology of the composite copper foil prepared with different components before and after electrolyte corrosion in this invention. Figure 3 This is a surface element distribution diagram of the composite copper foil prepared with different components in this invention before and after electrolyte corrosion; Figure 4 This is a schematic diagram of the electrochemical impedance spectroscopy (EIS) test of the composite copper foil prepared with different components according to the present invention after corrosion in the electrolyte; Figure 5 This is a schematic diagram of the polarization curve (Tafel) test of the composite copper foil prepared with different components according to the present invention after electrolyte corrosion; Figure 6 The images show the surface roughness of the composite copper foil prepared with different components before and after electrolyte corrosion. Detailed Implementation

[0022] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] Furthermore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0024] It should be understood that the singular forms used in this invention, such as "a," include plural references unless otherwise specified. Furthermore, the terms "comprising," "containing," and "having" are open-ended rather than closed-ended, meaning they include the contents specified in this invention but do not exclude other aspects. In other words, the terms also include "consistently made of" or "composed of."

[0025] Furthermore, "and combinations thereof" in the specification refers to any combination of all the listed items. The term "and / or" as used herein includes any and all combinations of one or more of the related listed items.

[0026] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter pertains. Where multiple definitions exist for a term, the definition herein shall prevail. Unless otherwise indicated, this invention employs standard nomenclature and standard laboratory procedures and techniques of analytical chemistry, organic synthetic chemistry, and optics.

[0027] The following detailed description illustrates the specific implementation method: Example 12

[0028] like Figure 1 As shown, a method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology includes the following steps: S1: Place a PI (polyimide) film flexible polymer substrate with a thickness of 20-26 µm in anhydrous ethanol and deionized water for ultrasonic cleaning for 0-0.5 hours. In this embodiment, a PI film flexible polymer substrate with a thickness of 25 µm is preferred, and the ultrasonic cleaning time is preferably 0.25 hours. Then, use a dryer to dry the polymer substrate for 0.2 hours to obtain the cleaned polymer substrate.

[0029] S2: The dried polymer substrate is placed in the magnetron sputtering chamber, specifically using tape to suspend the polymer substrate for double-sided deposition within the chamber. Then, a -300V self-bias voltage is used to perform plasma cleaning on the polymer substrate surface. In this embodiment, a Cu-Zn 9:1 (wt%) alloy is preferentially used as the target material, and deposition is performed using vacuum magnetron sputtering technology. The target material is a composite target with a stepped boss structure. The upper substrate of the composite target is composed of a Cu-Zn 9:1 (wt%) alloy, and the lower substrate is a Cu substrate.

[0030] The distance between the target and the polymer matrix is ​​150 mm, and the vacuum level of the magnetron sputtering equipment chamber is 3.0 × 10⁻⁶. -3 The sputtering power of the Pa, Cu-Zn alloy target was 100 W, the coating temperature of the polymer substrate was 28 °C, the gas flow rate was 35 sccm, the coating thickness on the polymer substrate was 1000 nm, and the sputtering time was 1 hour. Continuous thickening deposition was performed to obtain a Cu-Zn 9:1 (wt%) composite copper foil with a Cu-Zn 9:1 (wt%) coating thickness of 1000 nm and a metal-polymer composite film thickness of 27 µm.

[0031] S3: Using graphite as the target, a carbon layer was deposited on the surface of the Cu-Zn 9:1 (wt%) composite copper foil to obtain Cu-Zn@C polymer composite copper foil (i.e., Cu-Zn 9:1 (wt%)@C composite copper foil). The sputtering power of the graphite target was 200 W, the sputtering time was 3 hours, the coating temperature of the polymer substrate was 28 ℃, the gas flow rate was 35 sccm, the coating thickness on the polymer substrate was 200 nm, the bias voltage was -10 V, and the metal-polymer composite film thickness was 27 µm. The SEM image of the prepared Cu-Zn 9:1 (wt%)@C composite copper foil surface is shown below. Figure 2 As shown in (e).

[0032] Example 2

[0033] The difference from Embodiment 1 above is that this embodiment mainly uses magnetron sputtering technology to deposit a Cu-Zn 9:1 (wt%) alloy coating on the surface of the polymer substrate. The preparation process of the metal-polymer composite copper foil (hereinafter referred to as the composite film) includes the following steps: S1: A 25 µm thick PI (polyimide) film flexible polymer substrate was ultrasonically cleaned in anhydrous ethanol and deionized water for 0.25 hours respectively; then the polymer substrate was dried in a dryer for 0.1 hours to obtain the cleaned polymer substrate.

[0034] S2: The dried polymer substrate is placed in the magnetron sputtering chamber, and the surface of the polymer substrate is then plasma-cleaned using a -300V self-bias voltage. A Cu-Zn 9:1 (wt%) alloy is used as the target material, and deposition is performed using vacuum magnetron sputtering technology. The target material is a composite target with a stepped boss structure. The upper substrate of the composite target is composed of a Cu-Zn 9:1 (wt%) alloy, and the lower substrate is a Cu substrate.

[0035] The distance between the target and the polymer matrix is ​​100 mm, and the vacuum level of the magnetron sputtering equipment chamber is 1.5 × 10⁻⁶.-3 The sputtering power of the Pa, Cu-Zn 9:1 (wt%) alloy target was 100W, the coating temperature of the polymer substrate was 26 ℃, the gas flow rate was 30 sccm, the coating thickness of the polymer substrate was 700 nm, and the sputtering time was 1 hour.

[0036] S2: Continue with thickening deposition to obtain a Cu-Zn 9:1 (wt%) composite copper foil. The Cu-Zn 9:1 (wt%) coating thickness is 700 nm, and the metal-polymer composite film thickness is 26 µm. The SEM image of the prepared Cu-Zn 9:1 (wt%) composite copper foil is shown below. Figure 2 As shown in (a).

[0037] Example 3

[0038] The difference from Embodiment 2 above is that this embodiment mainly involves depositing a Cu-Zn 9.5:0.5 (wt%) alloy coating on the polymer substrate surface using magnetron sputtering technology, including the following steps: S1: The PI film flexible polymer matrix with a thickness of 25µm was ultrasonically cleaned in anhydrous ethanol and deionized water for 0.25 hours respectively; then the polymer matrix was dried in a dryer for 0.2 hours to obtain the cleaned polymer matrix.

[0039] S2: The dried polymer substrate is placed in the magnetron sputtering equipment chamber, and the surface of the polymer substrate is then plasma-cleaned using a -300V self-bias voltage. In this embodiment, Cu-Zn 9.5:0.5 (wt%) is preferentially used as the target material, and deposition is performed using vacuum magnetron sputtering technology. The target material is a composite target material with a stepped boss structure. The upper substrate of the composite target material is composed of a Cu-Zn 9.5:0.5 (wt%) alloy, and the lower substrate is a Cu substrate.

[0040] The distance between the target and the polymer matrix is ​​100 mm, and the vacuum level of the magnetron sputtering equipment chamber is 3.0 × 10⁻⁶. -3 The sputtering power of the Pa, Cu-Zn 9.5:0.5 alloy target was 100W, the coating temperature of the polymer substrate was 28 ℃, the gas flow rate was 55 sccm, the coating thickness of the polymer substrate was 800 nm, and the sputtering time was 1 hour.

[0041] S2: Continue with thickening deposition to obtain a Cu-Zn 9.5:0.5 (wt%) composite copper foil. The Cu-Zn 9.5:0.5 (wt%) coating thickness is 1000 nm, and the metal-polymer composite film thickness is 27 µm. The SEM image of the prepared Cu-Zn 9:1 (wt%) composite copper foil is shown below. Figure 2 As shown in (c).

[0042] The specific test experiments are as follows: (1) EIS test like Figure 4 Electrochemical impedance spectroscopy (EIS) results for different composite thin film samples in Examples 1-3 are presented. The differences in their corrosion resistance are mainly reflected in the changes in interfacial charge transfer resistance (Rct). The Rct of the Cu-Zn 9.5:0.5 (wt%) thin film in Example 3 decreased to 1.24 × 10⁻⁶. 3 The value of Ω·cm² indicates that the non-uniform distribution of a small amount of Zn on the surface creates a potential difference, inducing localized micro-galvanic corrosion. This makes charge transport easier in grain boundaries and defect regions, leading to a deterioration in corrosion resistance. When the Zn content is increased to Cu-Zn 9:1 (wt%), the Rct of the composite copper foil in Example 2 significantly increases to 1.22 × 10⁻⁶. 4 Ω·cm 2 A higher proportion of Zn helps to form a dense ZnO or Cu2O composite passivation film on the surface. This film can effectively block the direct corrosion of the substrate by F⁻ and significantly increase the charge transfer resistance, thereby significantly improving the corrosion resistance of the film.

[0043] After further constructing a carbon layer on the surface of the composite copper foil in Example 2, the Cu-Zn 9:1 (wt%)@C composite film of Example 1 was obtained, and its Rct was further increased to 1.48 × 10⁻⁶. 4 Ω·cm 2 The carbon layer acts as a dense physical barrier to reduce electrolyte penetration; on the other hand, it mitigates the damage to the passivation film caused by volume changes and stress concentration during corrosion through its flexible buffering effect, while also regulating the interfacial charge distribution and inhibiting the formation of active corrosion sites.

[0044] Based on the above data, the Cu-Zn 9:1 (wt%)@C composite film of Example 1 exhibits the best impedance characteristics, reflecting the protective mechanism of the synergistic effect of "physical isolation - charge transfer suppression - stress buffering".

[0045] (2) Tafel test like Figure 5 As shown, the Tafel polarization results further reveal the differences in corrosion thermodynamic stability and kinetics among different samples. The self-corrosion potential E of Examples 2, 3, and 1 are also presented. corr The values ​​are 0.207, 0.349, and 0.448 V, respectively. corr The successively positive shift of the values ​​indicates that the corrosion tendency is gradually suppressed. In Examples 2, 3, and 1, the corrosion current density i... corr It is 6.87×10 -5 2.08×10-5 6.14×10 -6 mA / cm 2 This also proves that Cu-Zn 9:1 (wt%)@C composite copper foil has good corrosion resistance.

[0046] (3) SEM surface morphology analysis The surface morphology of the composite film of Example 3 with low zinc content was observed after etching, such as... Figure 2 As shown in (d), it exhibits more severe corrosion damage, with large, interconnected corrosion pits appearing in localized areas. In contrast, the corroded composite film of Example 2, as shown... Figure 2 As shown in (b), the corrosion degree of the composite film is significantly reduced, with only slight corrosion marks appearing on the surface, and the overall morphology remains intact, indicating that optimizing the zinc content can effectively improve the corrosion resistance and structural stability of the alloy film. The surface of the Cu-Zn 9:1 (wt%)@C composite copper foil, as shown... Figure 2 (f) The Cu-Zn composite film modified with carbon layer showed no significant surface changes under the same corrosion conditions, and its morphology remained highly consistent before and after corrosion. This result confirms that the carbon layer can effectively block corrosive media and significantly enhance the interfacial chemical stability of the material.

[0047] In addition, through Figure 3 The elemental distribution maps (EDS) of the surface before and after corrosion further reveal the elemental evolution. Before corrosion, the Cu and Zn elements on the surface of Example 2 (Cu-Zn 9:1) were uniformly distributed, as shown in the reference diagram. Figure 3 (a, b) The high signal intensity of Zn and the absence of obvious segregation confirm that an appropriate amount of Zn is distributed in the alloy coating through solid solution, which is beneficial for the formation of a uniform and stable passivation film. In Example 3 (Cu-Zn 9.5:0.5), the Zn signal on the surface before corrosion is sparse and shows localized enrichment. (Refer to...) Figure 3 (c, d) indicates that the low Zn content failed to alloy uniformly, resulting in uneven composition. After corrosion, obvious dissolution pits appeared in the Zn area on the surface of Example 3, and the O content at the corresponding locations increased significantly, indicating that Zn preferentially dissolved as an anode, inducing localized micro-galvanic corrosion.

[0048] refer to Figure 3 (e,f) In Example 1 (Cu-Zn 9:1@C), the C layer remained intact before and after corrosion. The Cu and Zn elemental signals remained essentially unchanged after corrosion, and no preferential loss or elemental segregation of Zn was observed. This demonstrates that the surface carbon layer not only physically isolated the electrolyte but also effectively suppressed the selective dissolution of Zn, maintaining the stoichiometric stability of the alloy layer. The EDS results are in high agreement with the SEM morphology, EIS, and Tafel measurements, further confirming the excellent corrosion resistance mechanism of the Cu-Zn 9:1@C composite structure.

[0049] (4) Surface roughness test like Figure 6 As shown, the change in surface roughness before and after corrosion provides a quantitative basis for evaluating the corrosion resistance of different films. After corrosion, the Ra value of the Cu-Zn 9:1 (wt%) composite film in Example 2 increased from 19.31 nm to 44.36 nm, a relatively small change, indicating that the Cu-Zn alloy film can effectively improve the corrosion resistance of the current collector. This is attributed to the solid solution strengthening effect of an appropriate amount of Zn, which can generate a more dense and stable Cu-Zn composite oxide layer than CuO in situ during the early stage of corrosion, thereby delaying the corrosion process.

[0050] In Example 3, the Ra value of the Cu-Zn 9.5:0.5 (wt%) composite film increased sharply from 8.00 nm to 151.19 nm. This phenomenon is due to phase instability and microphase separation caused by the mismatch in the composition ratio. A large number of microcouples are formed between Cu and the small amount of Zn, which accelerates the anodic dissolution of Zn and leads to severe damage to the material surface.

[0051] After the carbon coating was introduced, the Ra value of the Cu-Zn 9:1 (wt%)@C composite film in Example 1 increased slightly from 1.71 nm to 1.91 nm after corrosion, indicating that its surface integrity was almost undamaged. The carbon layer does not participate in the electrochemical reaction, thus avoiding the introduction of new local galvanic potential differences and maintaining the chemical stability of the interface.

[0052] In summary, the test results show that the method of this invention, which sequentially deposits a Cu-Zn alloy layer and a carbon layer on a polyimide substrate to form a composite copper foil structure, significantly improves the corrosion resistance, interfacial bonding strength, and surface stability of the film. It is more suitable for the manufacturing process of high-energy-density lithium batteries and solves the problems of large weight, high cost, insufficient flexibility, and poor corrosion resistance of traditional copper foils. This is conducive to promoting the development of lightweight, high-safety, and long-life energy storage devices.

[0053] Furthermore, when the battery is damaged by external force or short-circuited, the Cu-Zn alloy coating can work synergistically with the polymer material in the intermediate layer, utilizing the low melting point of zinc to accelerate local melting and quickly cut off current transmission. At the same time, the flame-retardant properties of the polymer matrix further inhibit thermal diffusion, forming a dual protection mechanism that effectively prevents battery thermal runaway.

[0054] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology, characterized in that, Includes the following steps: S1: The flexible polymer matrix is ​​ultrasonically cleaned; then the ultrasonically cleaned flexible polymer matrix is ​​dried for 0.1-0.2 hours to obtain the dried polymer matrix. S2: The dried polymer matrix is ​​placed in the magnetron sputtering equipment chamber for plasma cleaning. A Cu-Zn alloy is used as the target material, and polymer matrix deposition is performed by vacuum magnetron sputtering coating technology. S3: Using graphite as the target material, a carbon layer is deposited on the surface of the polymer matrix after deposition in S2 to obtain Cu-Zn@C polymer composite copper foil.

2. The method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology according to claim 1, characterized in that, The flexible polymer substrate is a PI film with a thickness of 20-26 µm. During the ultrasonic cleaning process, the flexible polymer substrate is ultrasonically cleaned in anhydrous ethanol and deionized water for 0-0.5 hours respectively.

3. The method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology according to claim 1, characterized in that, In S2, the polymer matrix is ​​subjected to plasma treatment on its surface using a -300V self-biased voltage.

4. The method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology according to claim 1, characterized in that, In S2, the target material is a composite target material with a stepped boss structure.

5. The method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology according to claim 4, characterized in that, The upper substrate of the composite target material with a stepped boss structure is made of Cu-Zn alloy, and the lower substrate is a Cu substrate.

6. The method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology according to claim 1, characterized in that, The dried polymer matrix was suspended by tape in the working chamber of the magnetron sputtering equipment for double-sided deposition.

7. The method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology according to claim 1, characterized in that, In S2, the magnetron sputtering operating parameters are as follows: the distance between the target and the polymer substrate is 100-150 mm, and the vacuum level of the magnetron sputtering equipment chamber is 1.5-3.0 × 10⁻⁶ mm. -3 The sputtering power of the Pa, Cu-Zn alloy target is 100-200 W, the coating temperature of the polymer substrate is 26-28 ℃, the gas flow rate is 30-55 sccm, the coating thickness of the polymer substrate is 700-1000 nm, and the sputtering time is 0.5-1 hour.

8. The method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology according to claim 1, characterized in that, In S3, the magnetron sputtering operating parameters are as follows: sputtering power of graphite target is 100-200 W, sputtering time is 1-3 hours, coating temperature of polymer substrate is 26-28 ℃, gas flow rate is 30-55 sccm, and coating thickness of polymer substrate is 60-200 nm.

9. The method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology according to claim 1, characterized in that, The Cu-Zn alloy is a Cu-Zn 9:1 (wt%) alloy.

10. The method for preparing Cu-Zn@C polymer composite copper foil based on magnetron sputtering technology according to claim 9, characterized in that, In S3, the overall thickness of the Cu-Zn@C polymer composite copper foil is 26-27 µm.

Citation Information

Patent Citations

  • Preparation method of composite copper foil without light transmission points

    CN117845285A

  • High-adhesion composite copper foil current collector and preparation method and application thereof

    CN118553919A